Possible Role of MADS AFFECTING FLOWERING 3 and B-BOX DOMAIN PROTEIN 19 in Flowering Time Regulation of Arabidopsis Mutants with Defects in Nonsense-Mediated mRNA Decay - Nasim, Zeeshan; Fahim, Muhammad; Ahn, Ji Hoon (Frontiers in Plant Science, 2017)
Eukaryotic cells use nonsense-mediated mRNA decay (NMD) to clear aberrant mRNAs from the cell, thus preventing the accumulation of truncated proteins. In Arabidopsis, two UP-Frameshift (UPF) proteins, UPF1 and UPF3, play a critical role in NMD. Although deficiency of UPF1 and UPF3 leads to various developmental defects, little is known about the mechanism underlying the regulation of flowering time by NMD. Here, we showed that the upf1-5 and upf3-1 mutants had a late-flowering phenotype under long-day conditions and the upf1-5 upf3-1 double mutants had an additive effect in delaying flowering time. RNA sequencing of the upf mutants revealed that UPF3 exerted a stronger effect than UPF1 in the UPF-mediated regulation of flowering time. Among genes known to regulate flowering time, FLOWERING LOCUS C (FLC) mRNA levels increased (up to 8-fold) in upf mutants, as confirmed by qPCR. The upf1-5, upf3-1, and upf1-5 upf3-1 mutants responded to vernalization, suggesting a role of FLC in delayed flowering of upf mutants. Consistent with the high FLC transcript levels and delayed flowering in upf mutants, levels of FLOWERING LOCUS T (FT) and SUPPRESSOR OF OVEREXPRESSION OF CONSTANS 1 (SOC1) mRNAs were reduced in the upf mutants. However, RNA-seq did not identify an aberrant FLC transcript containing a premature termination codon (PTC), suggesting that FLC is not a direct target in the regulation of flowering time by NMD. Among flowering time regulators that act in an FLC-dependent manner, we found that MAF3, NF-YA2, NF-YA5, and TAF14 showed increased transcript levels in upf mutants. We also found that BBX19 and ATC, which act in an FLC-independent manner, showed increased transcript levels in upf mutants. An aberrant transcript containing a PTC was identified from MAF3 and BBX19 and the levels of the aberrant transcripts increased in upf mutants. Taking these results together, we propose that the late-flowering phenotype of upf mutants is mediated by at least two different pathways, namely, by MAF3 in an FLC-dependent manner and by BBX19 in an FLC-independent manner.